Uranium and Sm isotope studies of the supergiant Olympic Dam Cu–Au–U–Ag deposit, South Australia. (1st May 2016) - Kirchenbaur, Maria; Maas, Roland; Ehrig, Kathy; Kamenetsky, Vadim S.; Strub, Erik; Ballhaus, Chris; Münker, Carsten
Abstract: The Olympic Dam Cu–U–Au–Ag deposit in the Archean–Proterozoic Gawler Craton (South Australia) is a type example of the iron oxide–copper–gold (IOCG) spectrum of deposits and one of the largest Cu–U–Au resources known. Mineralization is hosted in a lithologically and texturally diverse, hematite-rich breccia complex developed within a granite of the 1.59 Ga Gawler Silicic Province. Emerging evidence indicates that both the breccia complex and its metal content developed over ∼1000 Ma, responding to major tectonic events, e.g., at 1300–1100, 825 and 500 Ma. However, metal sources and exact mechanism/s of ore formation remain poorly known. New high-precision 238 U/ 235 U data for a set of 40 whole rock samples representing all major lithological facies of the breccia complex show a narrow range (δ 238 UCRM112a  = −0.56‰ to +0.04‰). At the scale of sampling, there is no correlation of δ 238 U with lithology, degree of alteration or U mineralogy, although ores with U > 5 wt.% have subtly higher δ 238 U values (−0.20‰ to 0.00) than the majority of samples (<0.7 wt.% U, −0.56‰ to −0.23‰). The new U isotope data are consistent with published data for uraninites from Olympic Dam, and with published results from high-temperature U deposits. They overlap completely with the range of δ 238 U values in granitoids (including the host granite, −0.18‰ to −0.32‰) and with estimates of the upper continental crust in general. This similarity suggests that Olympic Dam δ 238 U values reflects the crustal sources of U, which probably include felsic volcanic rocks and granitoids. The isotopic homogeneity suggests depositional mechanisms that involve minimal isotopic fractionation of U; alternatively, primary fractionation signatures may have been erased during the long history of the U mineralization. High-grade U ores may record isotopic neutron-capture effects related to fissionogenic neutrons. High-precision Sm isotope data for five high-U (>5 wt.% U, U/Sm ≫ 500) Olympic Dam ores define a neutron capture line, with correlated depletions in 149 Sm (up to ∼2 ε  units) and excesses in 150 Sm (up to ∼ 4 ε  units), but fission fragment contributions to Sm are below detection. These observations provide evidence for small-scale neutron-capture effects, with calculated neutron fluences of 10 15 to 10 16  n cm −2, similar to those observed in several Proterozoic and Phanerozoic U deposits. The apparent lack of fission fragment contributions in Olympic Dam high-grade ores can be explained with an age of U deposition, or re-deposition that is substantially younger than the initial 1.59 Ga age of the oldest IOCG-style mineralization. The results presented here thus (i) suggest uranium sources in common (likely igneous) upper crustal lithologies, (ii) support geochronological evidence for gradual addition of U in several stages over 1000 Ma at elevated temperatures of mineralization, and (iii) do not show the high δ 238 U signatures expected from low-temperature reworking of older low- δ 238 U ores.